1991
DOI: 10.1093/ajcp/96.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Infection of the Fetus: Histology and In Situ Hybridization

Abstract: Fetal tissues from 16 spontaneous abortions, two terminations, and one perinatal death, 18 of which were associated with maternal human parvovirus B19 infection, were examined for B19 infection by histology and in situ hybridization using a digoxigenin-labeled B19-DNA probe. In 15 spontaneous abortions and one termination, erythroblasts with intranuclear inclusions (lantern cells) reacted with B19-DNA by in situ hybridization. No internal or external fetal malformations were observed. Because 13 (86.7%) sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…1). The other striking finding in some marrows was the presence of intranuclear inclusion bodies, with morphologic characteristics consistent with those observed in tissues infected with Bi 9 and other parvoviruses (10)(11)(12) (Fig. 1).…”
Section: Resultssupporting
confidence: 79%
“…1). The other striking finding in some marrows was the presence of intranuclear inclusion bodies, with morphologic characteristics consistent with those observed in tissues infected with Bi 9 and other parvoviruses (10)(11)(12) (Fig. 1).…”
Section: Resultssupporting
confidence: 79%
“…Maternal infection, when transmitted to the fetus, results in destruction of fetal erythroid cells causing severe anemia, cardiac decompensation with universal hydrops [6,19] and in spontaneous abortion or stillbirth. Since therapeutic blood transfusions are effective in the majority of cases and malformations are rare, termination of pregnancy by induced abortion is not generally indicated.…”
Section: Parvovirus B19mentioning
confidence: 99%
“…In general, when an erythroblastoid placental pattern without a history of blood group incompatibility or an other explanation occurs and the conventional light microscopy is unsuccessful, parvovirus B19 infection should be considered in the differential diagnosis and immunostaining as well as molecular techniques should be used to determine the virus [19]. …”
Section: Parvovirus B19mentioning
confidence: 99%
“…Later in gestation, B19-derived IUFD is generally associated with fetal hydrops. 11,12 However two recently published case-control studies from Sweden suggested that B19 is also a common cause of non-hydropic late IUFD. 13,14 The concept of B19-derived non-hydropic late IUFD is not supported by the findings of others.…”
Section: Introductionmentioning
confidence: 99%